The impact of volunteering on the volunteer: findings from a peer support programme for family carers of people with dementia. (10th March 2016) - Charlesworth, Georgina; Sinclair, James B.; Brooks, Alice; Sullivan, Theresa; Ahmad, Shaheen; Poland, Fiona
Abstract: With an ageing population, there are increasing numbers of experienced family carers (FCs) who could provide peer support to newer carers in a similar care situation. The aims of this paper are to: (i) use a cross‐sectional study design to compare characteristics of volunteers and recipients of a peer support programme for FCs of people with dementia, in terms of demographic background, social networks and psychological well‐being; and (ii) use a longitudinal study design to explore the overall impact of the programme on the volunteers in terms of psychological well‐being. Data were collected from programmes run in Norfolk, Northamptonshire, Berkshire and four London boroughs between October 2009 and March 2013. The volunteer role entailed empathic listening and encouragement over a 10‐month period. Both carer support volunteers ( N = 87) and recipient FCs ( N = 109) provided baseline demographic information. Data on social networks, personal growth, self‐efficacy, service use and well‐being (SF‐12; EuroQol Visual Analogue Scale; Hospital Anxiety and Depression Scale; Control, Autonomy, Self‐Realisation, Pleasure‐19) were collected prior to the start of the intervention ( N = 43) and at either 3‐ to 5 month or 10 month follow‐up ( N = 21). Volunteers were more likely than recipients of support to be female and to have cared for a parent/grandparent rather than spouse. Volunteers were also more psychologically well than support recipients in terms of personal growth, depression and perceived well‐being. The longitudinal analysis identified small but significant declines in personal growth and autonomy and a positive correlation between the volunteers' duration of involvement and perceived well‐being. These findings suggest that carers who volunteer for emotional support roles are resilient and are at little psychological risk from volunteering.